ISOFLAVONES AGLICONE OF TEMPE MALANG FRIED SLICES - Yetti Mulyati Iskandar; Sri Priatni (Indonesian Journal of Chemistry, 2008)
Soybean fermentation was carried out by using mixed culture Rhizopus oligosporus C and Rhizopus oryzae L16 (1:1) as inoculum. Incubation places in an incubator at 30 oC for 5 days and assessment of β-glucosidase activity daily was investigated. Isoflavones aglicone of tempe produced in laboratory scale, tempe commercial and fried slices tempe from Malang were analized by chromatography technique. Bioconversion of isoflavonoida in soybean to isoflavone aglicone compounds can be caused by extracelluler enzyme b -glucosidase. The observation showed that fresh tempe Malang was obtained genistein content 15.57 mg/100 g defatted tempe higher than tempe produced from laboratorium scale that was 5.45 mg/100 g defatted tempe. However, genistein content of fried slices tempe from Malang content decreased 25%, that was 11.45 mg/100 g defatted tempe. Tempe prepared at laboratory had the highest specific activity of β-glucosidase at day two that was 1693 U/g protein.